Caesarean scar pregnancy: a 10 case series - Lisovaja, Ija (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A Caesarean scar pregnancy is challenging and difficult diagnosis that can cause such complications as uterine rupture, profuse haemorrhage and maternal death. There are many single reports in literature but only few case series. Nowadays, caesarean scar pregnancy is becoming more frequent, it is caused by an increasing number of operative deliveries. In this paper, 10 cases of caesarean scar pregnancy treated in the Gynecology Clinic of the Riga Eastern Clinical University Hospital over 6 years are analysed. One of 10 patients had no symptoms on the day of presentation, 4 patients had pain in their lower abdomen, 3 had spotting, 6 had vaginal bleeding, and 2 of them had bleeding after legal abortion. All patients had 1 or 2 caesarean section in their history. Gestational age of the pregnancy was estimated from 3 to 12 weeks by the last menstrual period. All 10 patients were treated surgically. One patient was treated with 75 mg Methotrexate p.o., 2 days course, but the therapy was unsuccessful. Nine of 10 patients had total or subtotal hysterectomy. In one case, excision of scar pregnancy was performed and uterus was preserved. The most common symptoms of caesarean scar pregnancy are pain in the lower abdomen, spotting and vaginal bleeding. The treatment depends on severity of symptoms, gestational age and surgical experience.